TELAAH KURIKULUM BAHASA ARAB PERGURUAN TINGGI ISLAM - Muhammad Jafar Shodiq (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2013)
Arabic is the language that taught in almost all Islamic educational institutions from elementary school through college. Students Islamic college graduates are ideally expected to have a powerful ability in Arabic. But, the fact show that among the fundamental weakness for the majority of graduates of Islamic education institutions, from the first graduate-level, intermediate and even university graduates are weaknesses in the field of Islamic Arabic in various linguistic aspects. This paper aims to describe the Arabic language curriculum in four PTI: UIN Sunan Kalidjaga, Palangkaraya STAIN, STAIN Bangka Belitung, and STAIN Palu.